Children's Spirituality in Early Childhood Education: Theory to Practice - Mata-McMahon, Jennifer (Taylor & Francis Group, 2023)
Cover -- Half Title -- Title -- Copyright -- Contents -- List of Figures -- Acknowledgments -- Foreword -- Preface -- Introduction -- Section I What Is Children's Spirituality? -- 1 Defining Spirituality and Differentiating It From Religion -- Differentiating Spirituality From Religiosity -- Defining Spirituality -- Spirituality as a Holistic View of Development -- Spirituality as an Innate Human Potential or Ability to Be Present -- Spirituality as the Ability to Connect and Relate (to Self, Others, and Other) -- Spirituality to Rediscover Life's Meaning and Purpose -- 2 Understanding Children's Spirituality in the Literature and Research -- Studies on Children's Spiritual Meaning-Making and Relationships (Including to/with God) -- Studies on Children's Spirituality in Education/Educational Settings -- Studies on Children's Identity Formation and Sense of Self Through Spirituality -- Section II Spirituality in the Classroom - What Do the Teachers Say? -- 3 Looking Into Early Childhood Teachers' Perceptions of Nurturing Spirituality -- Research on Educators' Perception on Spirituality -- 4 How Ms. Escarfuller's Spirituality Informs Her Pedagogy -- Defining Spirituality -- How Spirituality Informs Pedagogy -- Perfection -- Purpose -- It's All in Our Favor -- We Are Spiritual Beings, Energy, and Manifesters -- Full, Complete, and Equal -- Needs, Mattering, and Growth -- Montessori Human Tendencies and Pedagogy -- 5 Vignettes From Ms. Escarfuller's Classroom -- Choice: The Material Serves the Child -- Hands at Work -- Movement Revealing -- Gregariousness &amp -- Conversation -- Time &amp -- Pacing -- Openness &amp -- Acceptance -- Preparation as an Adult -- Listening for That Inner Voice -- Gratitude -- Finding Meaning - A Montessori Great Lesson: The Story of The Coming of the Universe -- Emotional Awareness -- Connection With Others: Friendship.